2016
DOI: 10.17159/sajs.2016/20150069
|View full text |Cite
|
Sign up to set email alerts
|

Treatment technology for brewery wastewater in a water-scarce country: A review

Abstract: Water is a scarce resource in many parts of the world; consequently the application of innovative strategies to treat wastewater for reuse is a priority. The brewery industry is one of the largest industrial users of water, but its effluent is characterised by high levels of organic contaminants which require remediation before reuse. Various conventional treatment methods such as anaerobic and aerobic systems, which are effective options because of their high removal efficiencies, are discussed in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
3
14
0
1
Order By: Relevance
“…These could be due to various processes that took place in the brewing industry as reported in the United Nations World Water Development Report (WWAP 2017). The analysis of physicochemical characteristic showed that raw brewery wastewater has high levels of organic matter, nutrients, and solids, which corroborates the study by Jaiyeola and Bwapwa (Jaiyeola and Bwapwa 2016).…”
Section: Brewery Wastewater Characteristicssupporting
confidence: 88%
“…These could be due to various processes that took place in the brewing industry as reported in the United Nations World Water Development Report (WWAP 2017). The analysis of physicochemical characteristic showed that raw brewery wastewater has high levels of organic matter, nutrients, and solids, which corroborates the study by Jaiyeola and Bwapwa (Jaiyeola and Bwapwa 2016).…”
Section: Brewery Wastewater Characteristicssupporting
confidence: 88%
“…Breweries generate large volumes of wastewater through a sequence of processes. Brewery wastewater has a high content of nutrients (nitrogen and phosphorus) [ 5 , 6 ]. Nitrogen primarily comes from malt, adjuncts and nitric acid used for cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly research is aiming at low cost, decentralized and environmental friendly approaches to control pollution from industrial wastewater [ 8 , 9 ]. Increasing efforts are also being made to develop innovative technologies that can recover and reuse wastewater [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rush of global beer giants to Africa is due to the strong prospects for increasing production capacity due to economic growth, the rapid population boom, the emergence of a middle class and the urbanization. The volume of beer sold in Africa is expected to grow by 5%, ahead of Asia (3%) and Europe (1%) [6]. In Africa, the average annual intake of beverages per person is 9 liters.…”
Section: Introductionmentioning
confidence: 99%